The Relationship Between Adherence to Taking Medication with the Level of Knowledge and Family Support in TB Patients at Kroya Health Centre, Cilacap Regency - Hidayat Sugeng Riyadi; Fauziah; Silma Kaaffah (LPPM Universitas Harapan Bangsa, 2024)
TB (Tuberculosis) patients in Indonesia are the 2nd highest in the world after India. The large number of TB patients in Indonesia is due to the lack of success in TB treatment due to patient non-compliance with medication regularly. Factors that affect non-compliance are low knowledge of TB patients and lack of family support. This study aims to determine the level of family knowledge and support, medication adherence, and determine the relationship between the level of knowledge and family support to medication adherence in TB patients at the Kroya Health Center, Cilacap Regency in 2024. This study uses a non-experimental method with cross-sectional data collection conducted in April-May 2024. The study population is all TB patients totaling 130 respondents who underwent treatment at the Kroya Health Center, Cilacap Regency from November 2023 to May 2024, and the research sample was 56 respondents. The conclusion of this study is that the knowledge level of TB respondents is the highest at 37.5% and 55.4%, and the adherence to taking medication at the Kroya Health Center is 30.4% and 57.1%. In this study, the highest TB patients were at a moderate level of knowledge (55.4%); family support is not supportive (96.4%) and medication adherence is low (30.4%) to moderate (57.1%). Testing with the chi-square method there was a relationship between the level of knowledge and medication adherence in TB patients (p-value 0.000), but there was no relationship between family support and medication adherence (p-value 0.268) in patients at the Kroya Health Center, Cilacap Regency with a r value of 0.541. The limitation of this study is that there is no follow-up on the respondents such as monitoring TB drugs so that the existing data is only data taken when filling out the questionnaire.